2022
DOI: 10.3325/cmj.2022.63.257
|View full text |Cite
|
Sign up to set email alerts
|

Experience with comprehensive pharmacogenomic multi-gene panel in clinical practice: a retrospective single-center study

Abstract: AimTo assess the prevalence of actionable pharmacogenetic interventions in patients who underwent pharmacogenetic testing with a multi-gene panel. MethodsWe retrospectively reviewed single-center electronic health records. A total of 319 patients were enrolled who underwent pharmacogenomic testing with the RightMed test panel using TaqMan quantitative real-time PCR method and copy number variation analysis to determine the SNPs in the 27 target genes. ResultsActionable drug-gene pairs were found in 235 (73.7%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Drug side-effects can be a great treatment obstacle, and PGx tackles this issue by providing solutions specifically tailored to patients’ genetic code. PGx can maximize the efficacy of drugs and minimize the debilitating side effects, ensuring the best healthcare is being administered to patients [ 86 , 87 ].…”
Section: Wgs Applications In Clinical Diagnosticsmentioning
confidence: 99%
“…Drug side-effects can be a great treatment obstacle, and PGx tackles this issue by providing solutions specifically tailored to patients’ genetic code. PGx can maximize the efficacy of drugs and minimize the debilitating side effects, ensuring the best healthcare is being administered to patients [ 86 , 87 ].…”
Section: Wgs Applications In Clinical Diagnosticsmentioning
confidence: 99%
“…Ove varijante mogu utjecati na aktivnost enzima, transportera i receptora koji sudjeluju u metabolizmu lijekova, što rezultira raz ličitim brzinama metabolizacije i individualnim odgovorom na terapiju. 17 Na temelju informacija dobi venih WGSom, moguće je personalizirati doze lije kova za svako dijete kako bi se postigla optimalna kon centracija lijeka u tijelu i postigao najbolji mogući te rapijski učinak. Specifične genske varijante u djeteta utječu na brzinu metabolizma lijeka ili na njegovu in terakciju s drugim tvarima u tijelu.…”
Section: Farmakogenomika U Pedijatrijiunclassified
“…Beta-blockers were found to be one of the most commonly used drugs in the therapy of patients who reported for pharmacogenetic counseling in our previous study [11]. The DPWG guideline includes recommendations for metoprolol dosing based on genotype, where a decrease in dose and titration are recommended for both intermediate and poor metabolizers [42].…”
Section: Beta-blocker Implicationsmentioning
confidence: 99%
“…Research efforts have shown that a vast majority of individuals carry single nucleotide polymorphisms (SNPs) that are relevant for drug metabolism; such is also the case in the Republic of Croatia, where it was shown that actionable gene-drug pairs were present in 73.7% of patients at the time of pharmacogenomic testing [11]. It is, therefore, prudent to systematically report the population-specific frequencies of the most relevant SNPs, as it carries the potential benefit of tailoring population-specific interventions that may bring long-term health and economic benefits [12].…”
Section: Introductionmentioning
confidence: 99%